Bistatic Spaceborne-Airborne Experiment TerraSAR-X/F-SAR: Data Processing and Results - Rodríguez-Cassolà, Marc; Baumgartner, Stefan V.; Krieger, Gerhard; Nottensteiner, Anton; Horn, Ralf; Steinbrecher, Ulrich; Metzig, Robert; Limbach, Markus; Prats, Pau; Fischer, Jens; Schwerdt, Marco; Moreira, Alberto (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2008)
Following an original proposal by the authors to the TerraSAR-X (TSX) scientific coordination board, a spaceborneairborne bistatic experiment was successfully performed early November 2007. TSX was used as transmitter and DLR's new airborne radar system, F-SAR, as receiver; due to the capability of the latter to acquire data quasi-continuously, no echo window synchronisation is needed. Monostatic data were also recorded during the acquisition. This paper includes description and results of the spaceborne-airborne bistatic experiment, with special focus on data processing and image comparison. Given the acquisition scenario, with two-channel sampling and transmitter and receiver clocks operating independently, data processing must necessarily follow a three-step strategy: 1) channel balancing, 2) data synchronisation and 3) bistatic SAR processing. Since neither absolute range nor Doppler references are available in the bistatic data set, synchronisation is done with the help of calibration targets on ground and based on the analysis of the acquired data compared to expected data. Due to the variant nature of the bistatic acquisition and the required precision for the processing, data are processed using a bistatic backprojection approach. © 2008 IEEE.
DLR Import::2019-04-03